2017
DOI: 10.1016/j.egja.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different size Quincke spinal needles in reduction of incidence of Post-Dural Puncture Headache (PDPH) in Caesarean Section (CS). Randomized controlled study

Abstract: Background: Regional analgesia first introduced in clinical practice by the German surgeon Karl August Bier (1898). Spinal, epidural or combined spinal and epidural anaesthesia became the first line of choice in obstetric surgery. PDPH was found to be more frequent after Caesarean Section in young parturients. Also PDPH is related to CSF leakage from the subarachnoid space. Objectives: This prospective, double blinded, randomized study compares the frequency of PDPH following spinal anaesthesia for CS and tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
(25 reference statements)
2
10
0
1
Order By: Relevance
“…8,14 Time of appearance of CSF was significantly prolonged with 26 G Quincke spinal needle (14.60±2.56 sec) as compared to 4.14±1.81 seconds and 11.48±2.59 sec in group 1 and group 2 respectively. Similar observation was noted by Shah et al and Mohammed et al 6,10 CSF detection time directly depends on internal diameter of the needle. Smaller the internal diameter, greater is the time of detection.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…8,14 Time of appearance of CSF was significantly prolonged with 26 G Quincke spinal needle (14.60±2.56 sec) as compared to 4.14±1.81 seconds and 11.48±2.59 sec in group 1 and group 2 respectively. Similar observation was noted by Shah et al and Mohammed et al 6,10 CSF detection time directly depends on internal diameter of the needle. Smaller the internal diameter, greater is the time of detection.…”
Section: Discussionsupporting
confidence: 85%
“…6 Mean time of onset of SB was recorded and was observed highest in group 3 in our study. It was observed that needle with least internal diameter results in delayed onset of SB Similar findings was observed by Mohammed et al 10 This delay in the SB can be due to reason that fine gauge needle causes increased resistance which results in prolonged injection time of LA and hence delay in onset of block. Maximum height of SB achieved was noted and was observed that large number of patients achieved block till T8 in all the three groups.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations